(untitled) (Research, Society and Development, 2024)
Objective: to characterize patients with stroke treated at a hospital in the south of Santa Catarina. Methods: This is a cross-sectional study which evaluated 125 patients treated at a hospital in the south of Santa Catarina. Data collection took place between October and December 2022, using a proprietary data collection instrument, which was collected via medical record research. Results: Most of the patients treated are male, with an average age of 66.8 years and a prevalence of ischemic stroke. The risk factor most associated with patients was systemic arterial hypertension, followed by diabetes mellitus. Most of the patients studied were discharged. The most prevalent complication was infection. Conclusions: Based on the results of this study, it is crucial that urgent prevention and control measures are taken to reduce the number of people affected by stroke by providing better education and control of cardiovascular risk factors, mainly hypertension, overweight, obesity and DM2.